BCG protects toddlers during a tuberculosis outbreak. Issue 5 (3rd February 2009) - Gaensbauer, J T; Vandaleur, M; O'Neil, M; Altaf, A; Ní Chróinín, M
Abstract : In 2007, an outbreak of tuberculosis occurred in a toddler population attending two child care centres in Cork, Ireland. Of 268 children exposed, 18 were eventually diagnosed with active tuberculosis. We present the initial clinical and radiographic characteristics of the active disease group. Mantoux testing was positive in only 66% of cases. All cases were either pulmonary or involved hilar adenopathy on chest radiograph; there were no cases of disseminated disease or meningitis. 24% of the exposed children had been previously vaccinated with BCG, and no case of active disease was found in this group (p = 0.016), suggesting a profound protective effect of BCG in this population. Our experience provides evidence supporting a protective effect of BCG against pulmonary disease in young children.